(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article discusses the possibilities of an ergonomic approach in teaching English, corresponding to the levels of assimilation. The features of synchronous and asynchronous online learning methods are given. At the same time, it was emphasized that the best training option is a mixed method. The use of computers and an ergonomic approach in a gender aspect leads to the intensity of learning, increases motivation and independence of the learner.